2006
DOI: 10.1002/fedr.200511084
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and species composition of epiphytic bryophytes and lichens – a comparison of managed and unmanaged beech forests in NE Germany

Abstract: SummaryThe impact of forest management on the species diversity and species composition of epiphytic bryophytes and lichens in beech forests (Fagus sylvatica) of NE Germany was analysed. The investigations were carried out in one unmanaged and in one managed forest, with 45 sample plots of 400 m 2 each. In the sample plots, the presence of the epiphytes on 2 -4 randomly chosen trees (100 trees per forest) and seven environmental variables were recorded. The total number of species and the mean lichen density p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 31 publications
11
48
1
4
Order By: Relevance
“…Other authors found significant differences of species richness between intensive and extensive management regimes (Dettki and Esseen, 1998) or between managed and unmanaged forests (Friedel et al, 2006), indicating that not intensively managed or undisturbed stands host a richer lichen flora. Our non-significant differences between the two types of management were probably related to the relatively long rotation period of the shelterwoodcut sites, which allowed the development of species-rich communities dominated by crustose pioneer lichens and common generalist species.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors found significant differences of species richness between intensive and extensive management regimes (Dettki and Esseen, 1998) or between managed and unmanaged forests (Friedel et al, 2006), indicating that not intensively managed or undisturbed stands host a richer lichen flora. Our non-significant differences between the two types of management were probably related to the relatively long rotation period of the shelterwoodcut sites, which allowed the development of species-rich communities dominated by crustose pioneer lichens and common generalist species.…”
Section: Discussionmentioning
confidence: 98%
“…In general, epiphytic lichens are known to be sensitive to forest habitat disturbance (Aude and Poulsen, 2000;Giordani, 2012;Hauck et al, 2013;Johansson, 2008;Nascimbene et al, , 2013aPyk€ al€ a, 2004) their response often being detectable in terms of replacement of forest specialists with generalist species (Friedel et al, 2006;Matteucci et al, 2012;Nascimbene et al, 2007;Rogers and Ryel, 2008). Severe shifts in lichen composition are also associated with the invasion of alien trees, such as black locust (Robinia pseudoacacia), that replace native temperate forests .…”
Section: Introductionmentioning
confidence: 97%
“…No studies have included different regions, management types and developmental stages, along with detailed information on site conditions [13]. Furthermore, rather than addressing all lichen species in defined areas of differently managed forests, only corticolous species on individual trees were usually recorded [18], [19]. In addition, studies on the effects of stand age or stand characteristics on lichen species richness are rare outside Fennoscandia, where case studies have been carried out (e.g.…”
Section: Introductionmentioning
confidence: 99%